(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
The purpose of monitoring the parliamentary activity carried out in the Madrid Assembly, the subject of this parliamentary chronicle, is to offer information related to the fourth session of the XII Legislature, which runs from January 1 to June 12, 2023.